Production of N-acetylgalactosaminyl-transferase 2 (GalNAc-T2) fused with secretory signal Igκ in insect cells - Stuchlová Horynová, Milada; Takahashi, Kazuo; Hall, Stacy; Renfrow, Matthew B; Novák, Jan; Raška, Milan (Protein expression and purification, 2012)
The human UDP-N-acetyl-α-d-galactosamine:polypeptide N-acetylgalactosaminyl-transferase 2 (GalNAc-T2) is one of the key enzymes that initiate synthesis of hinge-region O-linked glycans of human immunoglobulin A1 (IgA1). We designed secreted soluble form of human GalNAc-T2 as a fusion protein containing mouse immunoglobulin light chain kappa secretory signal and expressed it using baculovirus and mammalian expression vectors. The recombinant protein was secreted by insect cells Sf9 and human HEK 293T cells in the culture medium. The protein was purified from the media using affinity Ni-NTA chromatography followed by stabilization of purified protein in 50mM Tris-HCl buffer at pH 7.4. Although the purity of recombinant GalNAc-T2 was comparable in both expression systems, the yield was higher in Sf9 insect expression system (2.5mg of GalNAc-T2 protein per 1L culture medium). The purified soluble recombinant GalNAc-T2 had an estimated molecular mass of 65.8kDa and its amino-acid sequence was confirmed by mass-spectrometric analysis. The enzymatic activity of Sf9-produced recombinant GalNAc-T2 was determined by the quantification of enzyme-mediated attachment of GalNAc to synthetic IgA1 hinge-region peptide as the acceptor and UDP-GalNAc as the donor. In conclusion, murine immunoglobulin kappa secretory signal was used for production of secreted enzymatically active GalNAc-T2 in insect baculovirus expression system.
Keywords: Solubility; myši; Animals; HEK293 Cells; Protein Stability; transfekce; aktivace enzymů; Enzyme Activation; genetické vektory; Amino Acid Sequence; Immunoglobulin A; Humans; Molecular Sequence Data; Recombinant Fusion Proteins; plazmidy; HEK293 buňky; Plasmids; stabilita proteinů; Baculoviridae; sekvence aminokyselin; N-Acetylgalactosaminyltransferases; imunoglobuliny - kappa-řetězce; Transfection; hmyz; N-acetylgalaktosaminyltransferasy; lidé; Cloning, Molecular; Mice; zvířata; Culture Media; Tandem Mass Spectrometry; rozpustnost; Immunoglobulin kappa-Chains; tandemová hmotnostní spektrometrie; klonování DNA; kultivační média; Genetic Vectors; imunoglobulin A; Protein Sorting Signals; Insecta; rekombinantní fúzní proteiny; molekulární sekvence - údaje; proteiny - lokalizační signály